The first thing I want to do here is take what they gave me and break it up so it's more useful.

3

*x*

^{2}= 4

*y*= 12 can be broken into two equations:

3

4

*x*^{2}= 124

*y*= 12 *Note that we have parts of what we want in both equations (our

*x*^{2}is in the first equation, our*y*is in the second). Since we're looking for*x*^{2}*y*eventually (those two parts multiplied together), let's multiply our entire equations by each other:(3

*x*^{2})(4*y) = (12)(12)**12*

*x*^{2}*y*= 144*And now we're almost there! We want to know what*

*x*^{2}*y*is by itself, so just divide both sides by 12:

**x**^{2}

**y****= 12**

**That's choice (D).**

*x*= 2 (or -2) and

*y*= 3. HOWEVER, it's better practice to continue to solve directly for the expression

*x*

^{2}

*y*because we're not always going to be able to solve for the component parts on questions like this...at least not quickly.